How much is too much? (Part 2) International Olympic Committee consensus statement on load in sport and risk of illness. Issue 17 (17th August 2016) - Schwellnus, Martin; Soligard, Torbjørn; Alonso, Juan-Manuel; Bahr, Roald; Clarsen, Ben; Dijkstra, H Paul; Gabbett, Tim J; Gleeson, Michael; Hägglund, Martin; Hutchinson, Mark R; Janse Van Rensburg, Christa; Meeusen, Romain; et al.
Abstract : The modern-day athlete participating in elite sports is exposed to high training loads and increasingly saturated competition calendar. Emerging evidence indicates that inappropriate load management is a significant risk factor for acute illness and the overtraining syndrome. The IOC convened an expert group to review the scientific evidence for the relationship of load—including rapid changes in training and competition load, competition calendar congestion, psychological load and travel—and health outcomes in sport. This paper summarises the results linking load to risk of illness and overtraining in athletes, and provides athletes, coaches and support staff with practical guidelines for appropriate load management to reduce the risk of illness and overtraining in sport. These include guidelines for prescription of training and competition load, as well as for monitoring of training, competition and psychological load, athlete well-being and illness. In the process, urgent research priorities were identified.